Perjalanan Spiritual Mulla Sadra dalam Al-Hikmah Al-Muta`aliyah fi Al-Asfar Al-Aqliyah Al-Arba`ah - Miftah Sidik; Ihsan Ammar Fadhlurrahman (CV Kalimasada Group, 2025)
Reaching the peak of man's spiritual journey to his beloved (God) is the desired goal of many religious people. From ancient times until now, the way to reach the peak of spirituality is still being debated both from religious circles and even academics. Therefore, in understanding and implementing the peak of the journey, it is necessary to have a deep reading of the spiritual process itself. In this study the author offers the concept of a spiritual journey by examining one of Mulla Sadra's magnum opus, namely the book of al-Hikmah al-Muta'aliyah fi al-Asfar al-Aqliyah al-Arba'ah. the method used in this research uses qualitative research. The primary source used is the book of al-Hikmah al-Muta'aliyah fi al-Asfar al-Aqliyah al-Arba'ah. The secondary data used are texts relevant to the discussion. This study found four concepts of spiritual journey by passing through ontological aspects. The implications of the book Al-Hikmah Al-Muta'aliyah fi Al-Asfar Al-Aqliyah Al-Arba'ah in Mulla Sadra's thought are profound and cover many aspects of human life, including religion, philosophy, and spirituality. It is an important contribution to the development of Islamic thought, and continues to influence Islamic philosophical and spiritual thought today.